2012
DOI: 10.5802/aif.2697
|View full text |Cite
|
Sign up to set email alerts
|

The cofinal property of the reflexive indecomposable Banach spaces

Abstract: Abstract. It is shown that every separable reflexive Banach space is a quotient of a reflexive Hereditarily Indecomposable space, which yields that every separable reflexive Banach is isomorphic to a subspace of a reflexive Indecomposable space. Furthermore, every separable reflexive Banach space is a quotient of a reflexive complementably ℓp saturated space with 1 < p < ∞ and of a c 0 saturated space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…This operator cannot be extended onto the whole space AH. [8] constructed another separable L ∞ counterexample to the scalar-plus-compact problem. However it contains ℓ 1 and Lemma 4.3.…”
Section: Counterexamplesmentioning
confidence: 99%
“…This operator cannot be extended onto the whole space AH. [8] constructed another separable L ∞ counterexample to the scalar-plus-compact problem. However it contains ℓ 1 and Lemma 4.3.…”
Section: Counterexamplesmentioning
confidence: 99%
“…Our theorem can also be compared to [3] and [9], where it was shown that every separable reflexive Banach space (e.g., ℓ 2 ) is a quotient of a hereditarily indecomposable space, a highly non-classical class of Banach spaces recalled in Section 2. Analogously, by our result, many simplistic classical Banach algebras appear as quotient algebras of L(X) spaces, a class of indirectly defined, and thus more intractable, objects.…”
Section: Introductionmentioning
confidence: 99%